Expression of CD94 by ex vivo-differentiated NK cells correlates with the in vitro and in vivo acquisition of cytotoxic features. (3rd October 2017) - Hasmim, Meriem; Khalife, Nadine; Zhang, Yanyan; Doldur, Manale; Visentin, Geralidne; Terry, Stéphane; Giron-Michel, Julien; Tang, Ruoping; Delhommeau, François; Dulphy, Nicolas; Bourhis, Jean-Henri; Louache, Fawzia; et al.
ABSTRACT: The administration of ex vivo -expanded Natural Killer (NK) cells in leukemia therapy is still challenging, in part due to the difficulty to generate in sufficient quantities fully mature and functional NK cells and Identification of surface markers indicative of NK maturation and functionality is therefore needed. Here, based on the analysis of surface receptors of ex vivo -expanded NK cells, we identified CD94 as a surface marker correlating with high lytic potential against leukemic cell lines and immunological synapse formation. CD94-positive ex vivo -expanded NK cells displayed higher expression of NKG2 receptors and the adhesion molecule LFA-1, as compared with their CD94-negative counterparts. We also tested the in vivo anti-leukemic capacity of ex vivo -expanded NK cells against patient-derived acute myeloid leukemia cells. Although no anti-leukemic effect was detected, we noticed that only CD94-positive ex vivo -expanded NK cells were detected in leukemic mice at the end of the 2-week treatment. Moreover, flow cytometry analysis showed a subpopulation harboring CD94 (NK) and CD34 (leukemic cells) double staining, indicative of conjugate formation. Therefore surface expression of CD94 on ex vivo -differentiated NK cells emerged as an indicator of in vitro and in vivo killer cell functionality.